PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK UNTUK MENINGKATKAN PEMEROLEHAN MUFRODAT SISWA KELAS IV MI SUNAN BONANG MOJOKERTO - Roudotul Mufidah; Siti Sulaikho (Al-Lahjah, 2020)
The background of this research is the weakness of learning Arabic in fourth grade children at MI Sunan Bonang and the lack of teachers in learning media. The application of this Scrapbook media is expected to be able to become a learning medium to improve mufrodat memorization. In this study, researchers used the R&D (Research and Development) methodology, which is a research method used to produce certain products, and to test the effectiveness of these products. To produce certain products, research that is needs analysis is used and to test the effectiveness of these products. Data collection is done by observation, interviews, tests and documentation. Data analysis is done by giving meaning to the data that has been collected. And from that meaning it can be concluded that the results of the application of Scrapbook media can show developments in Arabic learning, the improvement is very good. Thus the Scrapbook media greatly affects the mufrodat memorization ability of fourth grade students at MI Sunan Bonang.